PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU MA MA’ARIF 9 KOTA GAJAH PURWOREJO KECAMATAN KOTA GAJAH KABUPATEN LAMPUNG TENGAH - Ari Saputra (UNISAN JURNAL, 2024)
This research aims to determine the leadership of the madrasa head at MA Ma’arif 9 Kota Gajah Purworejo in improving the performance of teachers at MA Ma’arif 9 Kota Gajah Purworejo. The approach used in this research is a qualitative approach with a case study method. Data collection used observation, interview and documentation study techniques with emphasis on informant data sources, namely: Madrasah principals, teachers and students to confirm the validity of the data obtained. Based on the research results, the head of the madrasah at MA Ma’arif 9 Kota Gajah Purworejo has a democratic leadership type and is very instrumental in carrying out his leadership as an educator, manager, administrator, supervisor, leader and motivator in improving performance in planning, implementation and evaluation learning in class, and always empowering human resources in decision making. The performance of teachers at MA Ma’arif 9 Kota Gajah Purworejo has carried out an analysis of the effective week, prota, prosem, availability of media syllabus, score list, and student attendance list. The performance of subject teachers in lesson planning is in the very good category. Teachers are disciplined in carrying out their duties as educators. In its implementation to improve teacher performance, the madrasa head has included teachers whenever there is training according to the field of study. Apart from that, the head of the madrasah also gives appreciation to teachers, although not in the form of material, but in the form of mental support and praise for continuing to develop their potential. Keywords: Principal, Leadership, Teacher Performance